Children and young people as geological agents? Time, scale and multispecies vulnerabilities in the new epoch. Issue 3 (3rd May 2020) - Hadfield-Hill, Sophie; Zara, Cristiana
ABSTRACT: In this paper we frame children as geological agents, very much part of epoch and biospherical processes, enfolded in Earth system changes. We draw on the experiences of Indian childhoods in a context where the land, water, animals, children's bodies and forests are being shaped by a politics of corporate city building. We analyse how children and young people contribute to Earth system changes and consider the everyday, multispecies consequences of living with anthropogenic urbanism. The paper shows how children's bodies are entangled with human and non-human forces; they are geological agents which challenge, negotiate and have cyclical and rhythmic relationships with land and resources. We argue that time, scale and multispecies vulnerabilities are important reference points in our thinking through anthropogenic processes and thus contribute to a more nuanced understanding of the place of children and young people in the new epoch.